Early Postoperative Outcomes of Temporary Intestinal Stoma Reversal Surgery - Bacha, Ziaullah; Ullah, Hafiz Niamat (Biological and Clinical Sciences Research Journal, 2025)
Temporary intestinal stoma closure is standard but can carry notable short-term morbidity. Early postoperative complications directly affect recovery, hospital stay, and costs. Robust local data can guide perioperative optimization. Objective: To determine the frequency of early postoperative outcomes after temporary intestinal stoma reversal surgery. Methodology: Three hundred ninety-six patients aged 20 to 60 years of either gender scheduled for temporary stoma reversal were enrolled for this study. Patients with diabetes or gastrointestinal carcinomas were omitted. A single experienced surgeon performed all reversal procedures. Patients were assessed within seven days postoperatively for complications such as surgical site infection, wound, small bowel obstruction, and anastomotic leak. Results: The mean age of the patients in this study was 41.60 ± 11.86 years, with male patients 225 (56.8%). The indications for the initial stoma were enteric perforation 215 (54.3%), trauma 131 (33.1%), and abdominal TB 50 (12.6%). The postop complications were surgical site infection 97 (24.5%), wound dehiscence 29 (7.3%), small bowel obstruction 27 (6.8%), and anastomotic leak 13 (3.3%). Conclusion: Early postoperative outcomes after temporary intestinal stoma reversal surgery were surgical site infection (24.5%), wound dehiscence (7.3%), small bowel obstruction (6.8%), and anastomotic leak (3.3%).